2015
DOI: 10.11648/j.ajns.20150404.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of Men in Family Planning Utilization at Edaga-Hamuse Town, Tigray, North Ethiopia

Abstract: Back Ground: Family planning is a key for slowing unsustainable population growth and the resulting negative impacts on the economy, environment, and national and regional development efforts. Men are also recognized to be responsible for the large proportion of ill reproductive health Suffered by their female partners. In addition; male involvement helps not only in accepting a contraceptive but also in its effective use and continuation. But men involvement in family planning at the study setting is rarely k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 20 publications
6
29
0
Order By: Relevance
“…Moreover, they often disapprove the utilization of family planning services by their wives based on several barriers. These findings are in line with the reports by others researchers who conducted cross-sectional survey in different parts of Ethiopia [8], [9], [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, they often disapprove the utilization of family planning services by their wives based on several barriers. These findings are in line with the reports by others researchers who conducted cross-sectional survey in different parts of Ethiopia [8], [9], [13].…”
Section: Discussionsupporting
confidence: 93%
“…However, lack of information and low level of education got considerable share. Studies conducted in the north, north-west, south-west and south central parts of the country imply lack of appropriate information, inaccessibility of family planning services, attitudes of men towards family planning, perceived fear of side-effects, cultural or religious oppositions and desire for more children are among main barriers of male involvement in family planning in Ethiopia [2], [8], [9], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…10 Male participation in contraceptive use improves women's uptake and continuity of family planning approaches by increasing spousal coordination and decreasing opposition. [11][12][13] Past research has also demonstrated that male non-involvement in family planning leads to a high incidence of contraceptive discontinuation among women. 14,15 Especially in SSA, like Ethiopia, men are key decision-makers in family planning.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Previous studies performed in various parts of Africa showed that male participation is mandatory to minimise contraceptive discontinuation rates. [11][12][13] However in Ethiopia, the magnitude of male involvement in family planning was significant. 11,25,26 Thus, identifying the barriers of male involvement is vital in the development and scale-up of evidence-based male-involvement family planning interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation